Islamic triangle concept of marital age: Indonesian experience - Fauzan Muhammadi; Eva Wulandari; M. Hajir Susanto (Legality : Jurnal Ilmiah Hukum, 2021)
Marriage is a sacred act that no one will doubt. The sacredness of marriage does not mean that every person could be married. There are legal competencies in Islam that every person should be aware of before doing any legal acts. Islamic law sets two indicators of legal age; both are bālig and rusydan. Indonesia has determined the age of 19 to be a formal legal age of Indonesian people for their marriage. Finding the connection between the two indicators and concluded age is worth studying. The article aims to correlate Islamic legal competence with the marriage readiness and triangle analysis of legal age marriage based on Indonesia's factual issues. The article was described and analyzed qualitatively and based on the normative legal review. The review found out that ahliyyatul adā` al-kāmilah is the appropriate phase-in doing all legal activities, including marriage. The concluded age of 19 by the Indonesian government is well-measured when it was analyzed through the three parallel concepts: maslahah, ra’iyyatul imam manūtun bil maslahah, and sadd al-zarī’ah, all of which allow valuable considerations based on actual problematic issues of underage marriage.